2012
DOI: 10.7554/elife.00093
|View full text |Cite
|
Sign up to set email alerts
|

Population structuring of multi-copy, antigen-encoding genes in Plasmodium falciparum

Abstract: The coexistence of multiple independently circulating strains in pathogen populations that undergo sexual recombination is a central question of epidemiology with profound implications for control. An agent-based model is developed that extends earlier ‘strain theory’ by addressing the var gene family of Plasmodium falciparum. The model explicitly considers the extensive diversity of multi-copy genes that undergo antigenic variation via sequential, mutually exclusive expression. It tracks the dynamics of all u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
82
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(88 citation statements)
references
References 54 publications
5
82
1
Order By: Relevance
“…Mathematical models of competition between pathogen strains have demonstrated that immune selection can lead to maintenance of strain structure of discrete, nonoverlapping antigenic repertoires (21,25), although these studies address a finite number of variants at each locus in a closed system and much less diversity than that of the var genes in natural populations of P. falciparum. Artzy-Randrup et al (26) explored the special case of population structuring of the var multigene family. They used a computational model that simulates the dynamics of unique combinations of var genes in a population of hosts, which shows that, even with high recombination rates, the system can self-organize into a limited number of coexisting strains: the distinct var gene repertoires of these strains only weakly overlap, suggesting that the immune response of the host population has been partitioned into distinct niches (26).…”
mentioning
confidence: 99%
“…Mathematical models of competition between pathogen strains have demonstrated that immune selection can lead to maintenance of strain structure of discrete, nonoverlapping antigenic repertoires (21,25), although these studies address a finite number of variants at each locus in a closed system and much less diversity than that of the var genes in natural populations of P. falciparum. Artzy-Randrup et al (26) explored the special case of population structuring of the var multigene family. They used a computational model that simulates the dynamics of unique combinations of var genes in a population of hosts, which shows that, even with high recombination rates, the system can self-organize into a limited number of coexisting strains: the distinct var gene repertoires of these strains only weakly overlap, suggesting that the immune response of the host population has been partitioned into distinct niches (26).…”
mentioning
confidence: 99%
“…The questions of how strain diversity varies as intervention progresses and reduces transmission, (i.e., how rapidly and to what extent) are not well understood, although diversity is known to decrease with prevalence geographically. The consequences of this variation for vaccination should be investigated with more complex, agent-based models such as in Artzy-Randrup et al (64), where exposure to different variants can explicitly be represented, as well Fig. 4.…”
Section: Discussionmentioning
confidence: 99%
“…An important assumption is that natural immunity wanes, which is based on evidence showing that antibodies to merozoites antigens are relatively short-lived compared with antibodies to other pathogens, such as measles, that confer lifelong immunity (67) (report half-lives of 0.8-7.5 y). In addition, although immunity against PfEMP1 can be long-lasting [as has been shown for example for antibodies to Pfvar2 chondroitin sulfate A (Pfvar2-CSA)], an effect of waning immunity would still arise due to the diversity of these antigens in endemic regions [see, e.g., the simulations with the agent-based model in Artzy-Randrup et al (64), where PfEMP1 diversity is explicitly incorporated]. That is, for this large and diverse multicopy gene family, at the epidemiological level of the host population, an effect of waning immunity arises when individuals are exposed to specific variable surface antigens like PfEMP1 that they have not encountered before.…”
Section: Methodsmentioning
confidence: 99%
“…PfEMP1 is encoded by the var multigene family, with ∼60 copies present in each parasite genome. The degree to which boosting plays a role in maintenance of immunity will depend on the extent of overlap between the PfEMP1 repertoires of different strains (11)(12)(13)) and its precise effects on incidence of different clinical syndromes will also be affected by their different propensities to cause severe disease (14)(15)(16). The dynamics of boosting of CD8 + T-cell responses against the liver stages will also differ in important ways from boosting of antibodies to sporozoite or merozoite antigens.…”
mentioning
confidence: 99%